2019
DOI: 10.1089/ees.2018.0438
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Fluoride from Water Using Nanomaterials of Ferrihydrite, Apatite, and Brucite: Batch and Column Studies

Abstract: This study investigated the adsorptive removal of fluoride from simulated water pollution using various (hydro)oxide nanomaterials, which have the potential to be used as sorbents for surface water and groundwater remediation. Tested nanomaterials include hematite, magnetite, ferrihydrite, goethite, hematite-alpha, hydroxyapatite (HAP), brucite, and four titanium dioxides (TiO 2 -A [anatase], TiO 2 -B [rutile], TiO 2 -C [rutile], and TiO 2 -D [anatase]). Among 11 (hydro)oxide nanomaterials tested in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…α-Fe 2 O 3 ·H 2 O and β-Fe 2 O 3 ·H 2 O led to K d of PFOA increased from 0.292 to 0.437, 0.447 cm 3 ·g –1 (Table ). Previous research has indicated that compared to α-Fe 2 O 3 (0.10 mg·g –1 ), ferrihydrite (Fe 2 O 3 ·nH 2 O) enhanced adsorption potential (0.99 mg·g –1 ) for fluoride . The unique characteristics of ferrihydrite, including its substantial surface area and intricate pore structure, enable it to provide a broad surface and abundant adsorption sites available for PFOA adsorption …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Fe 2 O 3 ·H 2 O and β-Fe 2 O 3 ·H 2 O led to K d of PFOA increased from 0.292 to 0.437, 0.447 cm 3 ·g –1 (Table ). Previous research has indicated that compared to α-Fe 2 O 3 (0.10 mg·g –1 ), ferrihydrite (Fe 2 O 3 ·nH 2 O) enhanced adsorption potential (0.99 mg·g –1 ) for fluoride . The unique characteristics of ferrihydrite, including its substantial surface area and intricate pore structure, enable it to provide a broad surface and abundant adsorption sites available for PFOA adsorption …”
Section: Resultsmentioning
confidence: 99%
“…Proposed mechanism of PFOA transport and fate , and minerals transformation , considering the microbe–Fe x S y interaction in four PFOA-ion occurrence environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace et al (2019) investigated F-removal using Mg(OH) 2 -based adsorbents [20]. They conducted fluorine adsorptive removal tests on 11 types of nanomaterials, including brucite (a Mg(OH) 2 -based adsorbent), and reported that brucite was an adsorbent with excellent F-removal performance comparable to that of ferrihydrite and apatite.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded from batch test results that the F-adsorption behavior fit the Freundlich and Redlich-Petrson models better than the Langmuir model. Desorption tests were also performed during the column tests; however, the F-desorption efficiency (4-9%) was low, suggesting the difficulty in reusing the adsorbent [20].…”
Section: Introductionmentioning
confidence: 99%